2005
DOI: 10.1063/1.1868868
|View full text |Cite
|
Sign up to set email alerts
|

Bending experiment on pentacene field-effect transistors on plastic films

Abstract: We have fabricated very flexible pentacene field-effect transistors with polyimide gate dielectric layers on plastic films with a mobility of 0.3cm2∕Vs and an on/off ratio of 105, and have measured their electrical properties under various compressive and tensile strains while changing the bending radius of the base plastic films systematically. We have found that the change in source-drain current with bending radius is reproducible and reversible when the bending radius is above 4.6mm, which corresponds to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
175
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(199 citation statements)
references
References 11 publications
22
175
2
Order By: Relevance
“…When the effect of bending strain on electrical conduction property was systematically examined by freely bending the organic transistors, we found that the mobility increased or decreased by at least 10% upon the application of a strain of only approximately 1% depending on the bending direction. 2) It was demonstrated that changes in the channel current upon the application of strain were independent of the relationship between the current and strain directions but resulted from an electrical conduction phenomenon unique to polycrystalline organic semiconductors. In 2005, we also found that the minimum bending radius of the transistors was 1 mm or lower in the case of using a neutral-strain structure, which can reduce the strain In 2010, we succeeded in fabricating organic ultrathinfilm transistors and organic complementary metal oxide semiconductor (CMOS) integrated circuits with a drive voltage of 2 V that can maintain their electrical characteristics while being crushed (Fig.…”
Section: 3mentioning
confidence: 99%
“…When the effect of bending strain on electrical conduction property was systematically examined by freely bending the organic transistors, we found that the mobility increased or decreased by at least 10% upon the application of a strain of only approximately 1% depending on the bending direction. 2) It was demonstrated that changes in the channel current upon the application of strain were independent of the relationship between the current and strain directions but resulted from an electrical conduction phenomenon unique to polycrystalline organic semiconductors. In 2005, we also found that the minimum bending radius of the transistors was 1 mm or lower in the case of using a neutral-strain structure, which can reduce the strain In 2010, we succeeded in fabricating organic ultrathinfilm transistors and organic complementary metal oxide semiconductor (CMOS) integrated circuits with a drive voltage of 2 V that can maintain their electrical characteristics while being crushed (Fig.…”
Section: 3mentioning
confidence: 99%
“…One of the unique features of transistors manufactured on 1-μ m-thick substrates is their applicability to stretchable electronics: 42,[61][62][63] Stretchability is needed to adapt to surfaces that have non-zero Gaussian curvature. After fabrication of the devices, the electronic fi lm containing them is laminated onto a prestretched elastomer by simple picking and placing.…”
Section: From Ultrafl Exible To Stretchable Organic Transistorsmentioning
confidence: 99%
“…As discussed in detail later, a reduction in the total thickness of the devices can improve their mechanical fl exibility. [39][40][41][42][43] Therefore, new materials, processes, and device structures have to be explored. Organic thin-fi lm devices are expected to yield simultaneously large-area, lowcost, lightweight, and fl exible devices because they can easily be fabricated on polymer fi lms by printing processes such as inkjet printing.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the influence of compression or tensile strain on the electrical properties of TFTs, a systematic change of the bending radius during the electrical characterization has to be carried out. In general, compression or tensile strain causes reversible variations in the channel conductivity until a critical bending radius is reached, and the device is damaged by crack formation in the dielectric layer and delamination of the electrodes [79,80]. An enhancement of the flexibility properties can be achieved either by reducing the substrate thickness or an encapsulation of the TFTs in a sandwich construction between a sealant and the substrate [80].…”
mentioning
confidence: 99%
“…In general, compression or tensile strain causes reversible variations in the channel conductivity until a critical bending radius is reached, and the device is damaged by crack formation in the dielectric layer and delamination of the electrodes [79,80]. An enhancement of the flexibility properties can be achieved either by reducing the substrate thickness or an encapsulation of the TFTs in a sandwich construction between a sealant and the substrate [80]. Recently, Sekitani et al showed a low-voltage organic transistor fabricated on a 12.5 μm thick polymeric substrate covered with an encapsulation stack.…”
mentioning
confidence: 99%